A REVIEW Oral Sub Mucous Fibrosis: A Review - Sevlani, Sonia T; Gondkar, Sheetal; Saudagar, Ravindranath (Journal of Drug Delivery and Therapeutics, 2019)
Oral Sub Mucous Fibrosis is a well- recognized clinical entity, known since the time of Sushruta. In the modern literature OSMF was first reported by Schwartz (1952), Joshi (1953) was the first person to describe this entity in India. Oral Sub Mucous Fibrosis (OSMF) is a potentially malignant disease that results in progressive juxtaepithelial fibrosis of the oral soft tissues, resulting in increasing loss of tissue mobility, marked rigidity and an eventual inability to open the mouth. The basic change is a fibroelastic transformation of the connective tissue in the lamina propria followed by vesicle formation. It is a well-known chronic insidious disease, precancerous condition, an autoimmune and collagen related disorder whose origin is multifactorial and is associated with chewing of betel quid. It is characterized by progressive hyalinization of the lamina propria. In the later stages the oral mucous membrane becomes very stiff and the patient suffers from trismus and hence difficulty in eating. Earlier OSMF had been confined to countries like India, Pakistan, Bangladesh, etc., but now it is being reported from western countries as well. Inspite of intensive research over the years, a single etiologic factor for OSMF cannot be pointed out with certainty. Patients suffering with OSMF are initially present with a blanched or marble‑like pale mucosa, vesiculations and also show intolerance to hot and spicy food. The treatment of oral submucous fibrosis includes iron, multivitamins including lycopene, spirulina, pentoxifyline, colchicine local submucosal injections of steroids, hyaluronidase and chylomicrons, and surgical excision of the fibrous bands. Keywords: Oral Sub Mucous Fibrosis, juxtaepithelial fibrosis, oral soft tissues, fibroelastic, lamina propria, collagen.